Pemilahan Sampah Melalui Bank Sampah Berkah di Desa Sucenjurutengah - Nur Alfiah; Muhammad Muslih; Aini Munawaroh Nurd; Nur Ngazizah (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Waste is a collection of discarded materials originating from human and natural activities whose main function has been taken away. In 2022, based on data from the Min- istry of the Environment, total waste production in Indonesia will reach 67.8 million tons/year. This data shows that the level of waste production in Indonesia is very high. Therefore, there is a need for awareness among the public to manage waste so that it be- comes something that has use value. A waste bank is a place used to collect waste that has been sorted. Based on this situation analysis, it is necessary to carry out systematic, com- prehensive and sustainable activities which include reducing and handling waste. Various efforts continue to be made to change people's mindset that waste can provide many bene- fits, and this requires patience and a slightly longer process. Because there are still many people who are not aware of the importance of waste management. Therefore, it is neces- sary to establish a waste bank in Sucenjurutengah village. The existence of this waste bank is to maintain the cleanliness of the environment, providing blessings to the people of Sucenjurutengah. Waste management is very necessary to maintain environmental cleanli- ness. Because if the environment is not maintained or clean it will cause various problems, one of which will cause health problems.